Application of edge histogram descriptor and region shape descriptor to MRIs - Trojachanec, Katarina; Davcev, Dancho; Mircheva, Georgina (My University, 2009)
Medical images have a crucial place in the medical diagnosis. As a specific part of medicine, Magnetic Resonance Imaging (MRI) has become a useful modality since it provides plentiful information and high sensitivity. The rapid growth of MRI technology results in increasingly amount of MRIs which have to be efficiently stored, analyzed and described. By improving these processes, the decision making process for the clinicians is getting easier. In this paper we apply the Edge Histogram and the Region-based Shape descriptors standardized by MPEG-7 standard to MRIs. We have used 13917 MRIs provided by ImageCLEF 2008. Experimental results showed the Edge Histogram Descriptor achieves higher precision. We have also combined both descriptors by averaging their output ranks. Analysis showed that averaging the output ranks leads to higher precision. However, the obtained results and the fact that MRIs have specific characteristics suggest that additional image processing techniques have to be used.
Keywords: Magnetic Resonance Imaging (MRI), Content Based Image Retrieval (CBIR), MPEG-7, Edge Histogram Descriptor, Region-based Shape Descriptor